Особливості біохімічного складу плодів різних видів плодових рослин, інтродукованих на південному сході України. Повідомлення 1. Вміст аскорбінової кислоти - Mezhenskyj, V.M.; Mozhajeva, L.L.; Mezhenska, L.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The data about content of ascorbic acid in fruits of 82 species of fruit plants under the conditions of a South-East of Ukraine are presented. Species accumulating high quantities of ascorbic acid are determined. There are Rosa majalis – 458.1 mg/100 g (up to 843.0), Chaenomeles spp. – about 100.0 (up to 293.9), Shepherdia argentea – 113.1 (up to 169.0), Ribes nigrum – 97.7 (up to 124.1), Hippophaё rhamnoides – 56.9 mg/100 g (up to 169.0).